ARE OLDER ADULTS MORE WILLING TO DONATE? THE ROLES OF DONATION FORM AND SOCIAL RELATIONSHIP. (11th November 2018) - Zhang, F; Gong, X; Fung, H
Abstract: Whether older adults are more willing to donate money or time than younger adults is still under debate. In the current study, we investigated the age differences in donation willingness across different relationship and social distance. Eighty-nine younger and sixty-six older adults took part in a hypothetical donation task in which they were asked to donate money and time to relatives and nonrelatives at various social distances. Compared to younger adults, older adults a) donated less to nonrelatives (regardless of the donation form), but donated a similar amount (in money) or even more (in time) to relatives; b) displayed higher levels of kin selection in both monetary and time donations; and c) showed higher levels of social discounting (favoring socially close over distant others) in monetary but not time donation. The findings advanced the understanding about age differences in prosocial behaviors by underscoring the important roles of contextual factors.